Review of Islamic Business Ethics on Buying Practices of Round Coconut - Apriliani, Apriliani; Yatima, Khusnul (CV. Zabags Qu Publish, 2024)
This research aims to find out how the practice of buying and selling coconuts is made and reviewing Islamic business ethics in the practice of buying and selling round coconuts in Muara Sabak Ilir Village, Muara Sabak Timur District, East Tanjung Jabung Regency. The type of research that the author conducted was field research, using qualitative research methods and data collection techniques in the form of observation, interviews and documentation. Then for data analysis, the author uses data reduction methods, data presentation, and drawing conclusions. Based on cases in the field related to the practice of buying and selling round coconuts, there are two weighing methods that are often carried out, namely per kilo weighing and per seed weighing. In weighing each seed, the size of the coconut will be calculated equally). From the results of this research, it can be seen that from a review of business ethics in the practice of buying and selling round coconuts, it is still not in accordance with the principles of Islamic business ethics, because there are differences between farmers who have debt and those who have no debt. Where when coconut farmers have debt, they cannot choose which weighing method to use when buying and selling coconuts.